ANALISIS FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KEPUTUSAN PETANI MELAKUKAN ALIH FUNGSI LAHAN DARI SEKTOR PERTANIAN KE SEKTOR NON PERTANIAN DI DESA KARANGWIDORO KECAMATAN DAU KABUPATEN MALANG - Ahmad Mahmdud Kawirian; Ir. Sri Hindarti, M.Si; Dr. Masyhuri Machfudz, M.P (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This study has objectives including 1). Identifying the socio-economic conditions of the farming community that did and did not transfer the land in Karangwidoro Village. 2) Knowing the development of land use change in Karangwidoro Village in the period 2010 to 2019. 3). Know the socio-economic factors that influence farmers' decisions to transfer land functions. Determination of the sample used using the simple random sampling method (simple random sampling) as many as 39 samples of the farming community in Karangwidoro Village. This research uses descriptive data analysis and logit model regression statistics. Research results obtained include 1). There are differences in socioeconomic conditions between farming communities who do land conversion and do not do so. Farmers who do land conversion have an average income and land area smaller than farmers who do not do land conversion. 2). In the period of 9 years (2010-2019) there has been a decline in the area of agricultural land in Karangwidoro Village. Each year an average of 14.48% of the village's agricultural land is reduced and 6.8% of them switch to settlements. 3). Based on the results of logit regression analysis with a confidence level of 5%, two socio-economic variables were found that significantly affected the farmers' decision to transfer land, including land area with a significant value of 0.044 and 0.043 income.